2022
DOI: 10.1371/journal.pone.0265176
|View full text |Cite
|
Sign up to set email alerts
|

On heights and plains: How rodents from different habitats cope with three-dimensional environments?

Abstract: Dwelling in a specific habitat requires adaptation to the habitat physical and biological properties in order to maximize fitness. Adaptations that are manifested in the organization of behavior in time and space reflect how the environment is perceived and utilized. Testing species from different habitats in the same laboratory environment can uncover the differences in their behavior and their adaptations to specific habitats. The question posed in this study is that of how two rodent species, one occupying … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…Similarly, we found that sand rats and rats that dwell and forage in complex habitats were also biased towards the lower sectors [ 8 , 10 ]. This differed, however, in rocky habitat dwellers, the spiny mice, which preferred the upper sectors [ 9 ], whereas the flatland-dweller jirds preferred lower sectors and moved away from cliffs and upper sectors [ 9 , 10 ]. The bias towards descent rather than ascent has usually been interpreted in terms of energy cost.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Similarly, we found that sand rats and rats that dwell and forage in complex habitats were also biased towards the lower sectors [ 8 , 10 ]. This differed, however, in rocky habitat dwellers, the spiny mice, which preferred the upper sectors [ 9 ], whereas the flatland-dweller jirds preferred lower sectors and moved away from cliffs and upper sectors [ 9 , 10 ]. The bias towards descent rather than ascent has usually been interpreted in terms of energy cost.…”
Section: Discussionmentioning
confidence: 99%
“…Some of these studies focused on flying, swimming or swinging (e.g., bats [ 3 , 4 , 5 ]; fish [ 6 ]), while others focused on surface-bounded animals that in the real world may encounter sloping terrain, bushes, rocks, trees, and other forms of vertical structures. Studying the spatial behavior of surface-bounded animals indicated that they seem to display an attraction to the lower sectors and to horizontal surfaces [ 7 , 8 , 9 , 10 , 11 ]. However, some rodents also have climbing skills that are related to their habitat requirements [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This may facilitate three-dimensional navigation by receiving balanced vestibular cues [ 25 ] or help to avoid unbalanced muscular activity [ 19 ]. Additionally, the species' natural habitat plays a role in their reaction to the slope: species that live naturally in a complex environment are better at vertical exploration than those that live on plains [ 26 ]. Some species are also inclined to go down or up the slope—gravitaxis or anti-gravitaxis, respectively [ 24 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%